Test Items Validation in the Context of Education Export - I. A. Selivanova; I. Yu. Markovina; I. R. Ilyasov; A. K. Zhevlakova; R. P. Terekhov (Moscow Polytechnic University, 2020)
It is necessary to develop special assessment tools for international students, which will comply with the principles of evidence-based education. This is especially important in the context of Russian higher education export. Multiple choice questions (MCQs) are an essential part of the assessment and are suited for assessing the knowledge level of international students. The "Organic chemistry" is a basic course for pharmaceutical students, which is necessary for the understanding of principal subjects. The study objective was to develop a normative-oriented model of the "Organic chemistry" MCQs based examination for international students (the specialty 33.05.01 "Pharmacy") in accordance with the recommendations of the Association for Medical Education in Europe (AMEE). The previously developed interactive "Organic Chemistry Test Simulator", created at the Sechenov University, was used as the basis for the examination MSQs bank. It was analyzed by five independent experts, who work as teachers of organic chemistry. The average timing and the cut score were determined by the Angoff method, 90 sec and 64%, respectively. Among analyzed MCQs the 3% were found irrelevant, 22% were recommended for revision and modernization. Valid MSCs (600 items) served as the basis for the creation of extended examination MSQs bank. An algorithm for modeling the "Organic chemistry" MCQs based examination was proposed. The standardized examination test has 30 MSQs of different types. The standardized normative-oriented model of the "Organic chemistry" MCQs based examination for international students (the specialty 33.05.01 "Pharmacy") was validated in terms of relevance and representativeness, optimized in time and cut score.